INFLUENSE OF THE IONISING RADIATION ON STRUCTURE AND PROPERTIES OF NANODIMENSION POWDERS OF COPPER - Aliev, B.A. (Recent Contributions to Physics, 2018)
Methods of scanning electronic microscopy, x-ray diffractometry and small-angle x-ray dispersion are researched structure and structural characteristics of nanodimensional metal powders of copper before and after an irradiation high-energy electrons in an interval of dozes from 1 up to 10 МRad. From radiographic researches nano powders presence of new phases, with the changed structural parameters is certain. It is established that influence of ionizing influence leads to various structural reorganizations in a researched material.